Problem Based Learning Model For Increasing Problem Solving Skills In Physics Learning - Febri Yanto; Festiyed Festiyed; Enjoni Enjoni (STKIP Singkawang, 2021)
The role of creativity in learning is more associated with problem-solving activities, meaning that creativity is measured through the ability of students to approach and solve problems. However, the PBL model has not been implemented optimally by the teacher, so that the problem solving ability and learning achievement of students have not been optimally stimulated. This research study is proposed to develop a model of Problem-Based Learning to stimulate the improvement of the skill of problem solving in physics learning for students of Senior High School. The development of Problem-Based Learning model for physics learning applied the ADDIE model. The form of observation sheets, questionnaires and question sheets were used as the instrument of data collection. The product was validated by the experts and tested on the eleventh grade students of SMA 9 Padang with a value of 3.85 very valid categories.The practicality of the learning model was determined by the implementation of learning, teacher’s response and students’ response with a value of 3.73 with category done. The effectiveness of the learning model was determined by student activities, problem solving skills and knowledge aspect. show that Asymp.C. 001 <0.05 means that Ho is rejected. The research has found a Problem-Based Learning model for physics learning which is abbreviated with the problem based learning model to physics learning (PBL-PL) . The findings indicated that the Problem-Based Learning model can stimulate the improvement of students' problem solving skills for Physics learning in Senior High School. For this reason, it is recommended for the teachers and prospective teachers to apply the Problem-Based Learning model for Physics learning in Senior High School.